Assessment of biograft-HT with I-PRF graft in immediate dental implant placement - Arjun Singh Baghel; Pradyumna Kumar Sahoo; Jitender Sharma; Faris Jaser Almutairi; Heenal Girishbhai Adhyaru; Ritu Chhatbar; Atul Anand Bajoria (Wolters Kluwer Medknow Publications, 2023)
Objectives: This research was done to assess the efficacy of I-PRF and bone graft in immediate dental implant placement. Materials and Method: Twenty patients were selected randomly into 2 groups with 10 samples in each as Group I- using I-PRF and Group II with synthetic bone replacement alloplast (biograft-HT) after immediate implant placement. Postoperative clinical assessment after graft placement was done based on visual analog scale for pain, modified gingival index and modified plaque index at 2nd, 4th, and 6th months. A radiographic assessment of bone density was performed two and six months after the placement of the implant. Result: There was a statistically considerable variation between the change in modified plaque index and modified gingival index. There was a statistically insignificant divergence in the mean visual analog scale between the two groups at 1, 3, and 6 days. Group I demonstrated a higher change in bone density than group II, with a statistically significant difference (P = .002). Conclusion: An innovative, safe, and efficient method for controlling the healing process around immediate dental implants is provided by the use of I-PRF in conjunction with immediate dental implant placement.